Pengaruh Gaya Hidup Berbelanja, Tampilan Produk, Dan Potongan Harga Terhadap Pembelian Impulsif (Studi Kasus Pengguna Pada Shopee Mahasiswa FEB Unisma) - Sari, Novita; Asiyah, Siti; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this research is to determine the influence of shopping lifestyle, product display, and discounts on impulsive purchasing (Shopee users, FEB Unisma). The research method used is quantitative with data collection techniques through questionnaires distributed to 102 respondents, which were then analyzed using multiple linear regression with the help of SPSS25 application. The results of the study indicate that the variables of Shopping Lifestyle (X1), Product Display (X2), and Discounts (X3) have a simultaneous effect on the Impulsive Purchases of Shopee users among FEB Unisma students. Furthermore, partially, the variable Shopping Lifestyle (X1) has a positive and significant effect on the Impulsive Purchases of Shopee users among FEB Unisma students, the variable Product Display (X2) has a positive significant effect on the Impulsive Purchases of Shopee users among FEB Unisma students, and the variable Discounts (X3) has a positive significant effect on the Impulsive Purchases of FEB Unisma students using Shopee. Keywords : Shopping Lifestyle, Product Display, Discount, Impulsif Buying, Shopee Applications